Analisis Framing Berita Kekerasan Berbasis Gender Online di Media Liputan6.com dan Antaranews.com - Zikrina Munawarah (Jurnal Media dan Komunikasi, 2024)
This research aims to conduct a framing analysis of online gender-based violence (GBV) news presented by two prominent online media platforms in Indonesia, namely Liputan6.com and Antaranews.com. The phenomenon of online GBV has become increasingly significant with the growth of internet users and social media. In the context of the pandemic, the CATAHU report from the National Commission on Violence Against Women (Komnas Perempuan) indicates a dramatic increase in online GBV cases. This study adopts the framing analysis model proposed by Robert Entman to investigate how media framing constructions influence the public's understanding and perception of the online GBV issue. Liputan6.com focuses its reporting on online GBV in general, while Antaranews.com is more focused on the context of violence against female consumers by "debt collectors" on online lending platforms. Framing analysis includes stages such as Define of problem, Diagnose cause, Make moral judgement, and Treatment recommendation, highlighting the editorial perspectives on the root causes, moral evaluations, and recommended solutions. The research findings indicate that both media platforms emphasize collective responsibility in addressing the online GBV issue and demonstrate the interconnectedness of the issue with human rights and discrimination against women. This research provides insights into how online media constructs narratives around online GBV and its contribution to public understanding, shaping a narrative of collective responsibility in addressing the issue.